Sustainable and Community-Based Marine Tourism Development on Lovina Beach, Buleleng, Bali - I Gede Wiramatika; Rizki Sumardani; Fenny Sengkey; Rosvita Flaviana Osin; I Wayan Agus Anggayana (Politeknik Pariwisata Makassar, 2024)
Lovina, often known as Lovina Beach, is a marine tourism destination in Singaraja, North Bali. The tourism potential is still pristine and still maintains its authenticity. The most famous tourist attraction in Lovina Beach is the dolphin attraction. This study aims to describe the Lovina marine tourism destination, how local people participate in the development of Lovina tourist destinations and the obstacles faced by the community in developing Lovina tourist destinations. The research method used in the study is descriptive qualitative, data in this study were collected through observation methods, in-depth interviews, documentation, and literature studies. Determination of informants was determined using the Accidental Sampling technique. The results of this study describe tourist destinations seen from tourist destinations, tourist attractions, and tourism facilities. Community participation in the development of marine tourism destinations can be seen from maintaining the sustainability of biota, the formation of tourism awareness groups, the provision of tourism facilities, the provision of jukung (small boat) rentals, taking jobs in the tourism sector, and the holding of the Lovina festival. In the development of marine tourism destinations, there are several obstacles faced in the development of Lovina tourism destinations such as; the less than optimal arrangement and development of tourism potential which can be seen from the environmental pollution of Lovina Beach which greatly disrupts tourist activities. The conclusion drawn in this study shows that in the development of marine tourism destinations on Lovina Beach, local communities have been involved, but in its development, there are still obstacles that can be seen from the environmental pollution that occurs on Lovina Beach. Based on the findings in this study, the study recommends that in developing tourism, the community collaborates with the local government. Further research is recommended to examine the role of government and tourist perceptions.